Supplementation during pregnancy according to the most recent recommendations of the Polish Society of Gynecologists and Obstetricians - Paweł Paśko; Agnieszka Wiesner (Polish Pharmaceutical Society, 2021)
In July 2020, new recommendations of the Polish Society of Gynecologists and Obstetricians for supplementation during pregnancy has been published. The experts emphasized that the main source of vitamins, macro-, and microelements in pregnant women should not be multivitamin supplements, but a balanced and varied diet. However, they highlighted an important role of five active substances that are considered as the elementary components of supplementation during pregnancy, namely: folic acid, iodine, vitamin D, docosahexaenoic acid (DHA), and iron. This work aims to present the most recent recommendations of the Polish Society of Gynecologists and Obstetricians, in particular: the role, indications, contraindications, recommended daily dosage, and benefits of supplementation with the main five mentioned constituents, as well as their food sources, daily requirements in Polish population and possible results of deficiency and excessive intake. Summary of recommendations is as follows: Folic acid should be administered by all women in reproductive age, in dosage range 400-600 µg. Additionally, higher doses should be considered in women with the risk of folates deficiency and with positive history of neural tube defects. Iodine supplementation is recommended in all pregnant women, in dosage range 150-200 µg. In case of thyroid disease, monitoring of thyroid hormones concentrations, as well as thyroid-stimulating hormone (TSH) and thyroid antibodies levels is required. Due to high prevalence of vitamin D deficiency in our population, experts from Polish Society of Gynecologists and Obstetricians recommend administering vitamin D in dosage range 1500-2000 IU, in all pregnant and lactating women. Doses need to be enlarged to 4000 IU when higher risk of deficiency is suspected, e.g. in women with BMI > 30. Docosahexaenoic acid (DHA) should be supplemented by pregnant women in a dose of 200 mg, or higher - if the risk of premature birth occurs or low consumption of marine fish is reported. Iron supplementation, in a dose up to 30 mg, is recommended only for pregnant women with the iron deficiency anemia (Hb < 11 g/dl), and with low level of ferritin (< 60 µg/l). We believe that supplying the most up-to-date information on the topic of supplementation during pregnancy, would help pharmacists to provide pregnant women with professional advice about safe and effective supplementation, and hence contribute to the improvement of the pharmaceutical care quality in Poland.